Development of fin‐innervating motor neurons after peripheral target removal in medaka fish. Issue 2 (17th December 2020) - Chiba, Akina; Soma, Kenichi; Watanabe, Keisuke; Nagashima, Hiroshi; Sato, Noboru
Abstract: Peripheral targets regulate the development and survival of the nerve centers that serve them, because the elimination of the target normally results in massive death of the developing neurons that innervate it. This widely accepted theory appears to be well supported by developing limbs and their innervation in tetrapods, but it is unclear whether this concept applies to primitive vertebrates that have paired appendages. In this study, we examined the development of spinal motor neurons following pectoral fin bud removal (FBR) in medaka fish. After FBR, motor axons initially extended to the plexus region in a morphologically normal pattern. During the period of fin innervation, motor axons in the FBR‐medaka failed to form the normal brachial plexus and elongated ventrally toward the abdominal region. In the ventral horn that would normally innervate the pectoral fin, however, neurons did not undergo cell death following FBR. There were no differences in the numbers of axons in the ventral roots between the FBR and control sides. Motor neuron markers, RALDH2 and FOXP1, that are expressed in limb‐innervating motor neurons in the lateral motor column in tetrapods, were also expressed in the ventral horns of both the control and FBR sides in medaka fish. These results suggest that, although both tetrapod and medaka motor neurons share the same molecular characteristics for innervating paired appendages, the fates of neurons differ following the removal of their peripheral target. Therefore, the relationship between the peripheral target and its nerve center may be altered among vertebrates.